Stimulation model of qualified female sprinters individual running technique improvement - Anisimova, E. A.; Novikova, E. M.; Katenkov, A. N. (The Russian Journal of Physical Education and Sport, 2018)
Annotation. From a great variety of running kinds of track and field athletics 100 and 200 meters distances are the most difficult, as the speed of running increase is the function of the whole organism. The development of it demands deep knowledge of all factors and conditions, providing sports results increase. Materials. The model creation of the qualified sprinters` running technique development. It provides sports training system perception in an integral form. It helps to reveal the most effective directions of the running steps individual technique development. Research methods: scientific and scientific-methodical literature, highly-qualified coaches` progressive experience analysis and summarizing, shooting, modeling, pedagogical experiment, statistical data handling. Results. Scientific and scientific-methodical literature analysis showed that the main attention specialists pay to speed-power qualities development, the peculiarities of starting technique and starting stride mastering. Underestimating knowledge of sprinting physiological mechanism and the peculiarities revelation of the interaction mechanism with the support are one of the reasons for a slow competitive activity results increase. This article presents created by the authors model of individual running technique development among qualified female sprinters. It`s structural components provide an integral notion of the training process orientation and content. They, provide sprinters` competitive activity effectiveness increase. The expediency of this model use was proved during the pedagogical experiment. It was stated that the female runners from the experimental group achieved more considerable results within the same time period in comparison with the female athletes from the control group. It proves the perspectivity of the approach to sports training organization and realization among female sprinters by means of the training process preliminary modeling. Conclusion. During the model creation of the individual sprinting technique development among qualified female runners the character of interactions between the main components, their mutual influence, role and place in general system of sports training are revealed. It is very important for the training process organization, its logic, the main ides of athletes` improvement among qualified sprinters. Owing to modeling the following things become evident: the main regularities of sports results, approaches to the training load algorithm creation, differently directed exercises alternation increase.